Tests of conspecificity for closely related black fly (Diptera: Simuliidae) species of the Simulium striatum group in Thailand - Pangjanda, Sirinapa; Pramual, Pairot (Zootaxa, 2017)
Four black fly species of the Simulium striatum species group have been recorded in Thailand. These species are morphologically highly similar in all developmental stages except for the number and arrangement of the pupal gill filaments. In this study, we used multiple characters sources, including morphology, cytology, molecular biology and ecology, to test the hypothesis of conspecificity for S. quinquestriatum (Shiraki), S. nakhonense Takaoka & Suzuki and S. chiangmaiense Takaoka & Suzuki. A molecular study based on the cytochrome c oxidase subunit I (COI) was unable to separate these taxa. In contrast, the elongation complex protein 1 (ECP1) sequences clearly differentiate S. quinquestriatum from S. chiangmaiense and S. nakhonense. However, the latter two taxa could not be differentiated based on molecular DNA sequences. Simulium chiangmaiense and S. nakhonense are also similar in the larval habitat characteristics and have undifferentiated polytene chromosome banding patterns. Morphological examination of the number and arrangement of the pupal gill filaments found a number of intermediate forms. Therefore, S. chiangmaiense and S. nakhonense are apparently the same biological species that is polymorphic for the number and arrangement of gill filaments. Thus, we synonymized S. chiangmaiense with S. nakhonense.